Stroke in sickle cell disease: case report - Agarwal, Megha; Yadav, M. L.; Jaiswal, R. M.; Bansal, Pradeep Kumar (International Journal of Research in Medical Sciences, 2020)
Sickle cell disease is an inherited blood disorder that affects red blood cells. It is characterized by polymerization of haemoglobin, erythrocyte stiffening, and subsequent vaso-occlusions. These can lead to microcirculation obstructions, tissue ischemia, infarction and acute stroke. Transient ischemic attack, Ischaemic stroke, haemorrhagic stroke, silent cerebral infarction, headache, Moyamoya disease, neuropathic pain, and neurocognitive impairment are neurological complications of sickle cell disease. Here we report a case of ischemic stroke in a patient of sickle cell disease. For early diagnosis and proper management of sickle cell disease neurological complications require specialised haematological and neurological expertise. The newly used medications under ongoing research will be the hope to overcome this devastating disease and its complications.